Effects of Bitter Almond Oil on Some Biochemical Parameters in the Serum and Erythrocytes of Streptozotocin-Induced Diabetic Rats - Demır, Ersin; Keser, Serhat; Yılmaz, Ökkes (Zonguldak Bülent Ecevit Üniversitesi, 2015)
Diabetes is recognized as one of the most important diseases of our time, and it affects millions of people across the globe. The works of treat diabetes with plant-derived drugs continue for many years. In this study, we aimed to examine effects of the bitter almond oil on the live weight, fasting blood glucose levels and lipid-soluble vitamins, cholesterol, sterols, GSH, total protein and MDA levels in the serum and erythrocytes of Wistar rats, which forming experimental diabetes. 30 Wistar rats, 8-10 weekly aged, were randomly divided into three groups: 1. Control K 1mL/kg DMSO twice a week , 2. Diabetes D 45 mg/kg streptozotocin single dose + 1mL/kg DMSO twice a week , 3. Diabetes + Bitter Almond D+AB 45 mg/kg streptozotocin single dose + 1mL/kg bitter almond oil every day . According to our results, the fasting blood glucose level was significantly decreased and it was closed to the control group values in the D+AB group when compared to the D group. Also, when compared to the D group, the MDA level was significantly decreased in the serum of the D+AB group, its level was significantly increased in the erythrocytes of the same group, and the GSH level was significantly increased and it was closed to the control group values in the same group. The cholesterol level was decreased in the bitter almond given group when compared to the D group. In conclusion, it was observed that the fasting blood glucose level was decreased in the bitter almond oil given group. Particularly the cholesterol level was decreased in the serum and erythrocytes of the diabetic rats as a result of administration of the bitter almond oil. However, it can be suggested that the new advanced level studies may be do for better understanding of the reasons of this situation.

Diyabet çağımızın en önemli hastalıklarından biri olarak kabul edilmekte ve dünya genelinde milyonlarca insanı etkilemektedir. Bitkisel kaynaklı ilaçlarla diyabeti tedavi etme çalışmaları yıllardır sürmektedir. Bu çalışmada acı badem yağının deneysel olarak diyabet oluşturulan sıçanların canlı ağırlık ve açlık kan glukoz seviyeleri ile serum ve eritrositlerinde yağda çözünen vitaminler, kolesterol, steroller, GSH, total protein ve MDA düzeyleri üzerinde etkilerinin incelenmesi amaçlandı. 30 adet 8–10 haftalık Wistar erkek sıçan rasgele 3 gruba ayrıldı: 1. Kontrol K 1mL/kg DMSO haftada iki kez , 2. Diyabet D 45 mg/kg streptozotosin tek doz + 1mL/kg DMSO haftada iki kez , 3. Diyabet + Acı Badem D+AB 45 mg/kg streptozotosin tek doz + 1mL/kg acı badem yağı her gün . Sonuçlarımıza göre, D grubu ile karşılaştırıldığında, D+AB grubunda açlık kan glukoz düzeyinin anlamlı derecede azalarak K grubu değerlerine yaklaştığı belirlendi. Ayrıca D grubu ile karşılaştırıldığında D+AB grubunun serumunda MDA düzeyinin azaldığı, eritrositlerde ise MDA düzeyinin anlamlı düzeyde arttığı, GSH düzeyinin ise önemli düzeyde artarak kontrol grubu değerlerine yaklaştığı gözlendi. Kolesterol miktarının serum ve eritrositlerde acı badem yağı verilen grupta D grubuna göre azaldığı saptandı. Sonuç olarak acı badem yağı verilen grupta açlık kan şekeri seviyesinin azaldığı gözlenmiştir. Özellikle diyabetik sıçanların serum ve eritrositlerinde kolesterol seviyesinin acı badem yağı uygulaması sonucunda azaldığı gözlenmiştir. Fakat bu durumun sebeplerinin daha iyi anlaşılabilmesi için ileri seviyelerde çalışmalar yapılması önerilebilir
Acı Badem Yağının Streptozotosin Kaynaklı Diyabetik Sıçanların Serum ve Eritrositlerindeki Bazı Biyokimyasal Parametreler Üzerindeki Etkileri